Disentangling the Effects of Curvature and Misorientation on the Shrinkage Behavior of Loop-Shaped Grain Boundaries - Camerin, Fabrizio ; 0000-0003-2468-9351; Marín-Aguilar, Susana; Griffioen, Tim; Baltussen, Mathieu G.; Dullens, Roel P.A.; Van Der Meer, Berend; Dijkstra, Marjolein (Physical Review Letters, 2025)
The material properties of polycrystals are strongly affected by the evolution and coarsening of their internal grain structures. Yet, studying this process is challenging due to the complex interactions within grain boundary networks. Here, we systematically investigate the shrinkage of isolated loop-shaped grain boundaries in 2D colloidal crystals using a combination of simulations and experiments. Unexpectedly, we find that shear coupling decreases with increasing grain misorientation, contrary to geometric predictions. This counterintuitive result is attributed to enhanced concurrent sliding driven by the annihilation of dislocations. Furthermore, by focusing on the evolution of the grain size, we reveal a transition in shrinkage kinetics between small and large loop sizes, providing an explanation for previously observed discrepancies in grain boundary mobility. These findings reveal a more intricate dependence of grain boundary behavior on curvature and misorientation than previously reported, offering new insights into polycrystal coarsening dynamics.